SERUM NEUTROPHIL GELATINASE - ASSOCIATED LIPOCALIN (NGAL) AS A MARKER OF TUBULOINTERSTITIAL DAMAGE IN PATIENTS WITH CHRONIC GLOMERULONEPHRITIS - M.A. Dolinnaya (Ukrainian Journal of Nephrology and Dialysis, 2015)
Determining of serum creatinine level, glomerular filtration rate and albuminuria gives us no information about tubulointerstitial kidney damage. So it is especially important to search for non - invasive diagnostic methods that allow to diagnose early stages of tubulointerstitial kidney damage and start adequate treatment. This circumstance attempts to use neutrophil gelatinase - associated lipocalin (NGAL) to assess tubulointerstitial kidney damage in patients with chronic glomerulonephritis (CGN).The aim: to analyze the morphological picture of the kidneys in patients with CGN with arterial hypertension (AH) and without, to investigate the relationship between serum NGAL and histological indexes of tubulointerstitial kidney damage in CGN patients with saved renal function.Materials and methods. We examined 81 patients with CGN. Patients were divided into two clinical groups: CGN patients with AH, CGN without AH. We analyzed indicators of tubulointerstitial kidney damage according to vivo morphological study, level of serum NGAL.Conclusion: there is a correlation of varying strength between serum NGAL and indexes of tubulointerstitial kidney damage in CGN patients, strong direct relationship is found between serum NGAL and IF. Diagnostics of IF by determing ofserum NGAL is a highly sensitive and specific method with the efficiency of95.3%. Increase ofserum NGAL above 5ng/ ml indicates a high probability of the IF in CGN patients.Results. Patients with AH have more pronounced histological damage of tubulointerstitial tissue than CGNpatients without AH. Serum NGAL levels are higher in CGN patients with AH and without than in the control group. We find a correlation between serum NGAL and indicators of tubulointer - stitial kidney damage. Analysis of the diagnostic operating characteristics of interstitial fibrosis (IF) by determining of serum NGAL shows that this method is highly sensitive and specific, with an efficiency of95,3%. Constructing ofa non - linear model revealed that increase of serum NGAL level above 5 ng/ml indicates a high probability of the IF in CGN patients.